Word mingas oralitegraphies and mirrored visions on oralitures and indigenous contemporary literatures - Rocha Vivas, Miguel (North Carolina studies in the Romance languages and literatures, 2021)
"The mingas are traditional Indigenous meetings in which community members can come together to support each other in any kind of labor. In Colombia's Andean Southeast the mingas or minkas, a word that comes from Quechua-Aymara languages, are a prominent activity in projects that imply exchange, discussion of ideas, solidarity, and alliances. Mingas stand for processes of inter- and intra-cultural communication and cooperation. For the Pastos, a binational native community along the border of Colombia and Ecuador, what we commonly refer to as literature forms part of the collectively named and celebrated word mingas and thought mingas. This book partakes in this tradition of conversational exchanges and intercultural creative proposals. Word Mingas [Mingas de la palabra] focuses on oralitures and written literatures by self-identified Indigenous Colombian authors from the early nineties to the present, interweaving and comparing two threads of literary critique which I refer to as 'oralitegraphies' and 'mirrored visions,' respectively. As a point of departure, the earliest publications dealt with herein intersect with two of the most important events in Colombia's history: the 1991 Constitution in which Colombia declares itself a multiethnic and pluricultural country; and the protests surrounding the five-hundreth anniversary (1492-1992) of Europeans' colonization of the so-called Americas. The book focuses on the following works: Tengo los pies en la cabeza [I Have the Feet on My Head] (1992) by Berichá, an U'wa writer from the Sierra Nevada of Cocuy in the eastern Andes, Contrabandeo sueños con aríjunas cercanos [Smuggling Dreams with Arijunas Nearby] (1992) and Shiinalu'uirua shiirua ataal/En las hondonadas maternas de la piel [In the Skin's Maternal Folds] (2010), two poetry collections by the Wayuu writer Miguelángel López, who publishes under the pseudonym Vito Apüshana; the story 'Esa horrible costumbre de alejarme de ti' [This awful habit of leaving you] (1995) and the open letter to the President of Colombia by another Wayuu writer from the Guajira Peninsula, Vicenta Siosi Pino (2012); the poetry collection Samay pisccok pponccopi mushcoypa/Espíritu de pájaro en pozos del ensueño [A Bird's Spirit within the Depths of a Daydream] (2010) by Fredy Chikangana/Wiñay Mallki, a Yanakuna oralitor from Huila and Cauca in the central Andes; ten poems from the partially unedited Versos de sal [Verses of Salt,] one of whose authors is the Andoke-Uitoto writer from the Amazon Basin Yenny Muruy Andoque (Yiche); Bínÿbe oboyejuayëng/Danzantes del viento [Wind Dancers] (2005 and 2010) a work of oraliture by the Camëntsá writer from the Amazonian-Andean piedmont, Hugo Jamioy Juajibioy; the stories 'Manifiesta no saber firmar. Nacido: 31 de diciembre' [Declares Not to Know How To Sign. Born on December 31] (2006) and 'Daño emergente, lucro cesante' [Consequential Damage, Profit Loss] by the Afro-Wayuu writer Estercilia Simanca Pushaina; and Anmal gaya burba: isbeyobi daglege nana nabgwana bendaggegala/Significados de vida: espejo de nuestra memoria en defense de la madre tierra [Meanings of Life: A Reflection of our Collective Memory in the Defense of Mother Earth] (2011), a compilation of narratives and the doctoral work of Abadio Green/Manibinigdiginya, a Gunadule writer and researcher born in Panamá now residing in Colombia"--